Yeasts isolated from bovine rumen selected to degrade lignocellulosic roughage - EDUARDO ROBSON DUARTE; SABRINA MIRANDA LIMA; JULIANE COSTA NERE; CLAUDIO EDUARDO SILVA FREITAS; HIGOR ALEXANDRE RODRIGUES MAIA; ALINE DANIELA LOPES JÚLIO; FLÁVIA OLIVEIRA ABRÃO; JANETE MARIA SILVA ALVES; VERA LÚCIA DOS SANTOS; LUCIANA CASTRO GERASEEV; JÚNIO COTA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Duarte ER, Lima SM, Nere JC, Freitas CES, Maia HAR, Júlio ADL, Abrão FO, Alves JMS, Santos VLD, Geraseev LC, Cota J. 2024. Yeasts isolated from bovine rumen selected to degrade lignocellulosic roughage. Biodiversitas 25: 1159-1166. Commercial yeast strains are viable alternatives to chemical additives in ruminants; however, they are not self to the rumen ecosystem. The present study was conducted to compare the degradation of Urochloa decumbens (Stapf) R.D.Webster (UD) hay and sugarcane bagasse (SB) by eight selected yeast strains, naturally present in the rumen cows and control without microorganisms. Eight yeast isolates that showed >6 log CFU per mL of ruminal fluid were selected and identified as four Pichia kudriavzevii isolates, three Rhodotorula mucilaginosa isolates and one Candida tropicalis isolate, according to their morphological and physiological characteristics and by analyses of the D1 - D2 variable domain sequences of the 28S rRNA gene. The strain V5 (R. mucilaginosa) showed higher cell biomass production than other strains of this species in fermentations with UD (P<0.05). Two isolates of Pichia kudriavzevii (V10 and V62) and one of R. mucilaginosa (V5) promoted a higher reduction of dry matter (DM) of UD than other yeast. The strain V5 was also the most efficient to reduce DM of SB (P <0.05). These selected yeasts could represent a potential alternative for use in animal diets and for industrial applications.